Migrants' Remittances: Economic Lifeline but Fragile Support for Developing Countries. The Case of Belarus, Moldova and Ukraine (a Makroeconomic Perspective) - Burnete, S. (Київський національний університет імені Тараса Шевченка, 2016)
Today's economic development on a global scale is highly dependent on the free movement of factors of production across national borders in search of highest return in case of capital, highest compensation in case of technological and managerial capabilities, biggest pay envelope, in case of physical labor and so on. Although the latter has long been hampered from moving owing, on the one hand, to deterrence policies pursued by home countries' governments, and on the other hand, to barriers erected against immigration by host countries, legions of workers of various skills and abilities managed to shift to developed countries in order to find better-paid jobs. People heading for the West generally succeeded in saving significant shares of their earnings, which they would send to their families at home. The paper contains a comparative analysis aimed at ascertaining the effects of remittances on the economies of three ex-Soviet countries: Belarus, Moldova and Ukraine.

Економічний розвиток на сьогодні в глобальному масштабі сильно залежить від вільного руху факторів виробництва через національні кордони – в пошуках найвищої прибутковості, в разі капіталу, найвищої компенсації, в разі технологічних і управлінських можливостей, найбільшої заробітної платою, в разі фізичної праці і т.д. Хоча останній вже давно перешкоджає рухатися політика стримування, що проводиться урядами країн базування з одного боку, а з іншого боку, бар'єри, зведені проти імміграції приймаючих країн. Легіон працівників різних навичок і вмінь прагнуть перебратися в розвинені країни, щоб знайти більш високооплачувану роботу, щоб зберігати значну частку своїх доходів і посилати своїм родинам додому. У статті наводиться порівняльний аналіз з метою з'ясування впливу грошових переказів на економіку трьох країн колишнього СРСР: Білорусь, Молдова та Україна.
Грошові перекази мігрантів: економічна лінія життя, але крихка підтримка для країн, що розвиваються (кейс Білорусі, Молдови та України (макроекономічна перспектива))
Keywords: migration; remittance inflows; recipient countries; economic growth; міграція; приплив грошових переказів; країни-одержувачі; економічне зростання